Relationship between childhood abuse and substance misuse problems is mediated by substance use coping motives, in school attending South African adolescents. (1st January 2019) - Hogarth, Lee; Martin, Lindi; Seedat, Soraya
Highlights: Child abuse linked to drug problems in South African school attending adolescents. Drug use coping motives mediated this relationship. Prevention programs should target drug use coping motives. Abstract: Background: In adults, it has been shown that the relationship between childhood abuse and substance misuse problems is mediated by the belief that substance use helps cope with negative affective states. By contrast, in adolescents, it is unknown whether drug use coping motives play this same mediating role. Methods: Secondary analysis of 1149 school attending adolescents in Cape Town, South Africa (average age = 16.24 years, range = 13–23; 60% female). Questionnaire measures obtained during a single test session (among a larger battery) assessed childhood trauma (CTQ), alcohol (AUDIT) and drug problems (DUDIT), and coping orientation (A-COPE) which contained three items assessing drug use to cope with negative affect. Results: The three types of childhood abuse measured by the CTQ – emotional, physical and sexual – were positively associated with greater alcohol/drug problems, and drug use coping motives. Drug use coping motives mediated the relationships between childhood abuse types and alcohol/drug problems, and these mediational pathways remained significant when gender and other subscales of the A-COPE were included as covariates. Conclusions: These data are preliminary insofar as drug use coping motives were assessed with a non-validated subscale of the A-COPE. Nevertheless, drug use to cope with negative affect mediated the relationship between all three types of childhood abuse (emotional, physical, sexual) and alcohol/drug problems in school attending adolescents. The implication is that drug prevention programs for this risk group should seek to mitigate drug use coping motives.